The Influence of Compensation Motivation and Career Development on the Performance of Langgeng Jaya Mandiri Karanganyar Cooperative Employees - Shulha*, Hanifa; Wijiastuti, Sri; Widodo, Zandra (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
s research was conducted to determine the influence of compensation motivation and career development on employee performance at the Langgeng Jaya Mandiri Karanganyar Cooperative. Researchers used a case study at the Langgeng Jaya Mandiri Karanganyar Cooperative Company at the branch office and head office located in Pendem Village, Mojogedang District, Karanganyar Regency. The type of research approach is quantitative descriptive, data analysis techniques using descriptive test analysis, data quality testing, classical assumption testing, hypothesis testing and multiple linear regression testing. The data collection instrument used an online questionnaire with a sampling method using a saturated sample of 30 respondents. Based on the research, it can be concluded that motivation has a positive and significant effect on employee performance with a calculated t value of 5.716 and a significant value of 0.000. Compensation has a positive and significant effect on employee performance with a calculated t value of 3.719 and a significant value of 0.001. And career development has a positive and significant effect on employee performance with a calculated t value of 8.749 and a significant value of 0.000. Simultaneously, motivation, compensation and career development have a positive and significant effect on employee performance with a calculated F value of 463.244 and a significant value of 0.000. And employee performance variables are influenced by motivation, compensation and career development variables by 0.980 or 98%.